Health Care Expenditure and Income: A Global Perspective - Badi H. Baltagi; Raffaele Lagravinese; Francesco Moscone; Elisa Tosetti (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper investigates the long-run economic relationship between health care expenditure and income in the world using data on 167 countries over the period 1995-2012, collected from the World Bank data set. The analysis is carried using panel data methods that allow one to account for unobserved heterogeneity, temporal persistence, and crosssection dependence in the form of either a common factor model or a spatial process. We estimate a global measure of income elasticity using all countries in the sample, and for sub-groups of countries, depending on their geo-political area and income. Our findings suggest that at the global level, health care is a necessity rather than a luxury. However, results vary greatly depending on the sub-sample analysed. Our findings seem to suggest that size of income elasticity depends on the position of different countries in the global income distribution, with poorer countries showing higher elasticity.
Keywords: C31; C33; H51; 330; health expenditure; panels; income elasticity; world; exploring the geography of health